1981
DOI: 10.1007/bf02263642
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of transcobalamin II (TC II) in two families with TC II deficiency and related immunodeficiency

Abstract: Transcobalamin II (TC II) is an essential transport protein for vitamin B12 in blood. TC II can be separated into isoproteins by polyacrylamide gel electrophoresis. This method was used in combination with a specific radioimmunosorbent technique to evaluate genetic variants and inheritance of TC II‐deficient genes in relatives of two children with congenital TC II deficiency. Both patients presented with impairment of haematopoietic and immunological functions. Seven heterozygous individuals for TC II deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Cbl is converted into methyl-Cbl in the cytoplasm and 5'-deoxyadenosyl-Cbl in mitochondria and these two forms are utilized as coenzyme by methionine synthase and methylmalonyl-CoA mutase respectively. The essential role of TCII in the cellular delivery of Cbl for intracellular utilization is borne out by the fact that an inherited lack of TCII leads to intracellular Cbl deficiency, resulting in megaloblastic anaemia, impaired immune defence, neurological disorders (Hakimi et al, 1971;Hitzig et al, 1974;Burman et al, 1979;Hurani et al, 1979;Hall, 1981;Frater-Schroder et al, 1981;Thomas et al, 1982) and, in extreme cases, death if not treated with Cbl. Hereditary TCII deficiency is a rare autosomal recessive disorder (Hakimi et al, 1971) and three forms of TCII defect have been reported (Frater-Schroder, 1983). In the most common, immunoreactive TCII is absent from the plasma of TCIIdeficient patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cbl is converted into methyl-Cbl in the cytoplasm and 5'-deoxyadenosyl-Cbl in mitochondria and these two forms are utilized as coenzyme by methionine synthase and methylmalonyl-CoA mutase respectively. The essential role of TCII in the cellular delivery of Cbl for intracellular utilization is borne out by the fact that an inherited lack of TCII leads to intracellular Cbl deficiency, resulting in megaloblastic anaemia, impaired immune defence, neurological disorders (Hakimi et al, 1971;Hitzig et al, 1974;Burman et al, 1979;Hurani et al, 1979;Hall, 1981;Frater-Schroder et al, 1981;Thomas et al, 1982) and, in extreme cases, death if not treated with Cbl. Hereditary TCII deficiency is a rare autosomal recessive disorder (Hakimi et al, 1971) and three forms of TCII defect have been reported (Frater-Schroder, 1983). In the most common, immunoreactive TCII is absent from the plasma of TCIIdeficient patients.…”
Section: Introductionmentioning
confidence: 99%
“…Transcobalamin I1 deficiency is associated with megaloblastic anaemia, pancytopenia, immunologic, gastrointestinal, and mental disorders (Burman et al, 1979;Frater-Schroder, 1983;Frater-Schroder et al, 1981, 1982bHakami et al, 1971;Hall, 1981;Hitzig, 1974;Haurani et al, 1979;Seligman et al, 1980;Hoffbrand et al, 1984;Thomas et al, 1982). Pharmacologic doses of vitamin Biz allow normal hematological development.…”
Section: Introductionmentioning
confidence: 99%
“…The two latter alleles seem to be very rare, and T C II4s was observed in a patient with clinical symptoms due to a functionally defi cient T C II molecule [5,8]. In addition, a silent allele T C II" has been proposed [5,7], The mixtures arc degassed in vacuum before adding the catalyst (solution C) and T M E D .…”
Section: Introductionmentioning
confidence: 99%